Effect of solid to water ratio, time and temperature on aqueous extraction of gallic acid from labisia pumila var alata of Malaysia - Noor Adilah, Md Salehan; Nailaa, Aishath; Azilah, Ajit; Ahmad Ziad, Sulaiman (PCSIR Scientific Information Centre, 2020)
Labisa pumila var alata contains bioactive compounds such as gallic acid that is of use for pharmaceutical and nutraceutical industries. Aqueous extraction is the traditional method that extracts phytochemicals from plant material. The study aimed to find the optimum condition for maximum gallic acid yield from ground L. pumila leaves using aqueous extraction. The results revealed that the maxium gallic acid yield obtained was at 1:10 sample to water ratio for 8 h at 50 °C. The maximum yield of gallic acid obtained was 1.025 mg gallic acid per g dried leaves (mg/g). The identification of gallic acid was done on Liquid Chromatograph Mass Spectrometer Quadrupole Time-of-Flight (LCMS-Q-TOF) by comparison to that of reference standard. The morphological structure of the extract that was obtained at optimum condition showed less denaturation of cell wall which indicates that still some gallic acid could be trapped in the sample matrix and other methods need to be employed to release them.